Natural polymers in wound healing: From academic studies to commercial products. Issue 22 (12th April 2023) - Tavakoli, Mohamadreza; Labbaf, Sheyda; Mirhaj, Marjan; Salehi, Saeideh; Seifalian, Alexander Marcus; Firuzeh, Mahboubeh
Abstract: Natural biopolymers (carbohydrates and proteins) are the family of natural polymers that are widely used in wound healing. This is due to their biocompatibility and their chemical structural similarity to the extracellular matrix (ECM). Wound healing is a complex process and requires a multidisciplinary approach and appropriate treatment product to enable a full recovery. Chronic nonhealing wounds significantly caused the reduction. Currently, diabetic and nonhealing wounds are considered the unmet clinical need and a new effective treatment will benefit patients and the economy. This research was aimed to critically review both literature as well as industrial products that used carbohydrates and proteins in wound dressing for the treatment of the wound. The outcome was chitosan (CS), as a carbohydrate, has the most clinical application as it is readily available and affordable, and has shown excellent antibacterial activity. Among proteins, keratin (Kr) can be an option with similar characteristics, however, Kr has not yet found clinical use when compared with CS. Abstract : Common carbohydrates and proteins used in wound healing applications.